A Case of Carotid Body Tumor with Perineural Tumor Spread along the Superior Laryngeal Nerve - Way, Ashley Renay; Fiester, Peter; Holtzman, Adam; Rao, Dinesh (Journal of Clinical Imaging Science)
We report a case of a patient with a carotid body tumor with perineural tumor spread along the right superior laryngeal nerve. Perineural spread is most commonly associated with squamous cell, adenoid cystic, and mucoepidermoid carcinoma. To the best of our knowledge, this has not been reported previously with carotid body tumor.